Learn Angular your first week - Bodrov-Krukowski, Ilya; M, Manjunath; Houwens, Byron; Aden, Jason; Ribeiro, Claudio; Kolev, Kaloyan; Wilken, Jeremy; Wanyoike, Michael; Bouchefra, Ahmed; Softic, Vildan; Aden, David (SitePoint Pty. Ltd., 2018)
Angular is not just a framework, but rather a platform that empowers developers to build applications for the web, mobile, and the desktop. This book contains a collection of articles that provide a rapid introduction to Angular, getting you up and running with no fuss. It contains: Angular Introduction: What It Is, and Why You Should Use It by Ilya Bodrov-Krukowski AngularJS and Angular: a Detailed Comparison by Manjunath M An Introduction to TypeScript: Static Typing for the Web by Byron Houwens Getting Past Hello World in Angular by Jason Aden Angular Components: Inputs and Outputs by David Aden A Practical Guide to Angular Directives by Claudio Ribeiro Angular Components and Providers: Classes, Factories and Values by David Aden Quickly Create Simple Yet Powerful Angular Forms by Kaloyan Kolev Using Angular NgModules for Reusable Code and More by Jeremy Wilken Angular Testing: A Developer's Introduction by Michael Wanyoike Creating UIs with Angular Material Design Components by Ahmed Bouchefra Developing Angular Apps without a Back End Using MockBackend by Vildan Softic React vs Angular: An In-depth Comparison by Pavels Jelisejevs This book is for all front-end developers who want to get proficient with Angular and its related tools. You'll need to be familiar with HTML and CSS and have a reasonable level of understanding of JavaScript in order to follow the discussion.
Authors' names from chapter headings. - Includes bibliographical references. - Online resource; title from title page (Safari, viewed July 10, 2018)
Keywords: AngularJS (Software framework); Application software -- Development; Web applications; Web site development; Logiciels d'application; Développement; Applications Web; Sites Web; Développement; COMPUTERS; Programming; General; Application software; Development